ABUSE OF ECONOMIC AND POLITICAL POWER IN ELECTION CAMPAIGNS (CIPEEX, 2025)
This study provides a critical analysis of the abuse of economic and political power in Brazilian electoral campaigns, highlighting its impacts on democratic legitimacy, equal opportunities among candidates, and the free expression of popular will. The methodology combines bibliographic, normative, and jurisprudential research, examining scholarly works, legal provisions, and decisions of the Superior Electoral Court (TSE). Economic abuse is identified in the excessive use of financial resources, while political abuse occurs through the misuse of public machinery for electoral gain. Recent cases, such as lawsuits against the governor of Pará and against candidate Pablo Marçal, illustrate abusive practices involving the distribution of benefits, misuse of institutional communication, and commercialization of political support. Current legislation — notably Law No. 9,504/1997 and Complementary Law No. 64/1990 — provides sanctions such as annulment of registration or diploma and ineligibility, but enforcement is often weakened by procedural delays. Advances include the prohibition of corporate donations, the criminalization of undeclared campaign funds, and increased social awareness. However, significant challenges persist, including structural inequality, new forms of digital abuse, and weaknesses in real-time monitoring. Recommendations include strengthening oversight mechanisms through artificial intelligence, legislative improvements, reform of campaign financing, and political education. The study concludes that, although normative and institutional progress has been made, greater transparency, faster judicial processes, and more effective sanctions are essential to safeguard the integrity of the electoral process and representative democracy in Brazil.
Keywords: electoral law; abuse of power; democracy; Brazil